2022
DOI: 10.3389/fimmu.2022.884067
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Causing Acantholysis in Pemphigus-Lessons from Human Skin

Abstract: Pemphigus vulgaris (PV) is an autoimmune bullous skin disease caused primarily by autoantibodies (PV-IgG) against the desmosomal adhesion proteins desmoglein (Dsg) 1 and Dsg 3. PV patient lesions are characterized by flaccid blisters and ultrastructurally by defined hallmarks including a reduction in desmosome number and size, formation of split desmosomes, as well as uncoupling of keratin filaments from desmosomes. The pathophysiology underlying the disease is known to involve several intracellular signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 201 publications
0
19
0
Order By: Relevance
“…The p38MAPK signaling pathway is an important signaling pathway that mediates Dsg3 internalization followed by depletion from endosomes [18]. A previous study reported that the pathogenic activity of polyclonal PV IgG can be attributed to p38 MAPKdependent clustering and endocytosis of Dsg3, whereas pathogenic monoclonal Dsg3 antibodies can function independently of this pathway [19].…”
Section: Discussionmentioning
confidence: 99%
“…The p38MAPK signaling pathway is an important signaling pathway that mediates Dsg3 internalization followed by depletion from endosomes [18]. A previous study reported that the pathogenic activity of polyclonal PV IgG can be attributed to p38 MAPKdependent clustering and endocytosis of Dsg3, whereas pathogenic monoclonal Dsg3 antibodies can function independently of this pathway [19].…”
Section: Discussionmentioning
confidence: 99%
“…There may be many causes of primary acantholysis, the most known being pemphigus group diseases caused by autoantibodies against desmosome proteins. This condition can be caused by bacterial toxins, as in staphylococcal scalded skin syndrome, or by a genetic defect in the kertinocyte cell membrane, as in Hailey-Hailey disease [3][4][5].…”
Section: Loss Of Intercellular Cohesionmentioning
confidence: 99%
“…Skin blistering diseases are clinically polymorphic large-group disorders and they sometimes may be devastating. These disorders may be classified according to [1] the level of the blister: subcorneal, mid epidermis, suprabasal, subepidermal; [2] the mechanism of blister formation (spongiosis, acantholysis, blistering degeneration, or epidermolysis); and [3] the type of inflammation (neutrophilic, lymphocytic, eosinophilic, mixed) [1]. In this section, pemphigoid group diseases such as bullous pemphigoid, mucous membrane pemphigoid, acquired epidermolysis bullosa, linear IgA bullous dermatosis, and anti p-200 pemphigoid will be explained with a brief introduction to blistering diseases of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models of pemphigus, however, are hampered by the relatively complex experimental procedures ( 8 , 9 ) or by the differences in DSG expression patterns between mice and men ( 10 ). Organ skin models are being increasingly used to overcome these limitations and to implement the replace, reduce, and refine (3R) principles of animal research, including to replace animal experiments by appropriate alternatives ( 11 – 14 ). We recently developed a highly standardized human skin organ culture (HSOC) model of pemphigus using skin from donors of elective surgery ( 15 ).…”
Section: Introductionmentioning
confidence: 99%